(untitled) (Proceedings of the International Conference on Education, 2021)
Adolescence is a marked period of many changes both physical and psychological and are generated in the high levels of anxiety and frustration which can affect their academic performance and well-being especially at this time of pandemic. There is evidence of the benefits of Storytelling in education, such as the development of critical thinking, resilience, among others the use of technology and storytelling through the creation of videos to work and promote emotional intelligence in adolescents. PrepaTec Morelia students developed videos My Best Story, to promote positive emotions and emotional intelligence through anticipation, savoring, and reminiscence using the application Stop Motion Studio, SilentFilm Studio and LEGO movie maker. Our population was 240 students of High School enrolled in the class of Tutoring and Well-being, semester August-December 2020. Our main goal was to create stop motion videos using different video applications to promote emotional intelligence and positive emotions through savoring "anticipated memory" and reminiscence in the students of PrepaTec Morelia. As a first step, the students made what we call Story_Emotion_Map which consists of two parts: in the first step, students decide on the composition of their video, the characters, the analysis of the feelings experienced as well as any obstacles they have faced. Later, with this information, they wrote the script that should include its beginning, development and end, to later proceed to make the video. After applying an emotional inventory made up of 20 items on a five-point Likert scale, whose responses ranges from 1 (It never happens to me) to 5 (It always happens to me) which assesses mood, joy and optimism, grades of 3.26 were obtained in the initial emotional inventory with standard deviation of 0.57; at the final emotional inventory grades of 4.53 were obtained with a standard deviation of 0.15.